From Artifacts to Understanding: Transforming Museums into Contextual Learning Laboratories for Islamic Studies - Arifin, Muh Luqman; Yusufi, Adnan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study explores the educational potential of the Bumiayu Archaeological Museum as a medium for contextual learning in Islamic Studies. The museum houses a diverse collection of artifacts spanning prehistoric times, Hindu-Buddhist periods, and early Islamic eras, representing dynamic traces of local civilization. Employing a qualitative approach through an exploratory case study design, data were collected via observation, in-depth interviews, and documentation, then analyzed thematically. The findings reveal that the museum's artifacts possess historical, spiritual, and pedagogical values that can be harnessed to strengthen Islamic historical literacy and foster contextual understanding of Islamic teachings. The museum functions as an active learning laboratory, enabling students to comprehend relationships between Islamic texts and local historical-cultural contexts. Integrating the museum into a Contextual Teaching and Learning (CTL) framework proves effective in cultivating reflective, critical, and moderate attitudes toward understanding Islamic teachings among students.